2003
DOI: 10.1152/ajpgi.00455.2002
|View full text |Cite
|
Sign up to set email alerts
|

Peptide fragments of AMP-18, a novel secreted gastric antrum mucosal protein, are mitogenic and motogenic

Abstract: Antrum mucosal protein (AMP)-18 is a novel 18-kDa protein synthesized by cells of the gastric antrum mucosa. The protein is present in secretion granules of murine gastric antrum epithelial cells and is a component of canine antrum mucus, suggesting that it is secreted into the viscoelastic gel layer on the mucosal surface. Release of the protein appears to be regulated because forskolin decreased the amount of immunoreactive AMP-18 in primary cultures of canine antrum mucosal epithelial cells, and indomethaci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
112
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(121 citation statements)
references
References 30 publications
8
112
1
Order By: Relevance
“…Wound assays were performed as previously described (21,22). Briefly, confluent monolayers of cells grown in 6-well plates were incubated overnight in serum-free medium and then wounded using a blue pipette tip.…”
Section: Methodsmentioning
confidence: 99%
“…Wound assays were performed as previously described (21,22). Briefly, confluent monolayers of cells grown in 6-well plates were incubated overnight in serum-free medium and then wounded using a blue pipette tip.…”
Section: Methodsmentioning
confidence: 99%
“…GKN1 is a novel autocrine/paracrine protein that is specifically expressed in gastric mucosa (1,2). Toback and colleagues reported that GKN1 protects the antral mucosa and promotes healing by facilitating restitution and proliferation after injury (3). Interestingly, GKN1 is downregulated in Helicobacter pylori-infected gastric epithelial cells, and the loss of GKN1 expression is detected in gastric cancer tissues and precancerous lesions such as intestinal metaplasia (4,5).…”
Section: Introductionmentioning
confidence: 99%
“…Beside the important role in gastric mucosal protection 1,4,5 , the biological reason for the antiamyloidogenic properties of human GKN1 and for its role in APP processing in gastric tissues is unclear. One explanation might be assigned to the BRICHOS domain acting in general as a chaperon toward peptides with a tendency to asssume β-strand structure.…”
Section: Gkn1 and Its Role In App Processingmentioning
confidence: 99%
“…Gastrokine1 (GKN1), a 18 kDa protein also known as antrum mucosal protein (AMP-18) 1 , is highly expressed in the gastric mucosa of many mammals species 1,2 . The gene coding GKN1 (CA11), located on the chromosome 2p13 (accession number: BK0017373), is about 6 kb long and contains 6 exons.…”
Section: Introductionmentioning
confidence: 99%